Application-centric recovery algorithm for wireless sensor and actor networks. (1st January 2013) - Imran, Muhammad; Said, Abas Md; Younis, Mohamed; Hasbullah, Halabi
Sustaining actor-actor connectivity is extremely crucial in mission-critical applications of wireless sensor and actor networks where actors have to quickly plan optimal coordinated responses to detected events. This paper presents ACR; a novel hybrid application-centric connectivity restoration algorithm that factors in the application besides efficient resource utilisation while recovering from critical node failures. As a pre-failure planning measure to minimise recovery delay, ACR identifies the actors' primaries that are critical for network connectivity based on localised information and then designates for them backup nodes. The backup nodes are carefully picked to satisfy application concerns such as actor effectiveness. In order to minimise the impact of critical node failure on coverage and connectivity, ACR appoints high degree nodes with overlapped coverage. Upon failure detection, the pre-designated backup pursues controlled and coordinated movement to replace the failed node. We prove the convergence of ACR and analytically derive bounds on its performance. Simulation results further confirm the performance of ACR.